Improved outcomes after hypothermic oxygenated machine perfusion in liver transplantation-long-term follow-up of a multicenter randomized controlled trial - Czigány, Zoltán; Uluk, Deniz; Pavicevic, Sandra; Lurje, Isabella; Froněk, Jiří; Keller, Theresa; Strnad, Pavel; Jiang, Decan; Gevers, Tom; Koliogiannis, Dionysios; Guba, Markus; Tolba, Rene H.; et al. (Hepatology communications, 2024)
Background: - While 4 randomized controlled clinical trials confirmed the early benefits of hypothermic oxygenated machine perfusion (HOPE), high-level evidence regarding long-term clinical outcomes is lacking. The aim of this follow-up study from the HOPE-ECD-DBD trial was to compare long-term outcomes in patients who underwent liver transplantation using extended criteria donor allografts from donation after brain death (ECD-DBD), randomized to either HOPE or static cold storage (SCS). - Methods: - Between September 2017 and September 2020, recipients of liver transplantation from 4 European centers receiving extended criteria donor-donation after brain death allografts were randomly assigned to HOPE or SCS (1:1). Follow-up data were available for all patients. Analyzed endpoints included the incidence of late-onset complications (occurring later than 6 months and graded according to the Clavien-Dindo Classification and the Comprehensive Complication Index) and long-term graft survival and patient survival. - Results: - A total of 46 patients were randomized, 23 in both arms. The median follow-up was 48 months (95% CI: 41-55). After excluding early perioperative morbidity, a significant reduction in late-onset morbidity was observed in the HOPE group (median reduction of 23 Comprehensive Complication Index-points [p=0.003] and lower incidence of major complications [Clavien-Dindo ≥3, 43% vs. 85%, p=0.009]). Primary graft loss occurred in 13 patients (HOPE n=3 vs. SCS n=10), resulting in a significantly lower overall graft survival (p=0.029) and adverse 1-, 3-, and 5-year survival probabilities in the SCS group, which did not reach the level of significance (HOPE 0.913, 0.869, 0.869 vs. SCS 0.783, 0.606, 0.519, respectively). - Conclusions: - Our exploratory findings indicate that HOPE reduces late-onset morbidity and improves long-term graft survival providing clinical evidence to further support the broad implementation of HOPE in human liver transplantation.
Gesehen am 26.06.2024